Stereological Measurements of Cardiac Ultrastructures Implicated in Excitation-Contraction Coupling - Page, Ernest (1971)
Electron micrographs of osmium-fixed left ventricles from 200-g female rats were analyzed by stereological techniques. By the use of equations developed by H. Sitte it was possible to determine volume fractions of organelles and absolute membrane areas per unit cell volume for cellular membrane systems implicated in excitation-contraction coupling. The fractions of cell volume were: mitochondria 0.34, myofibrils 0.481, T-system 0.012, total sarcotubules 0.035, other 0.13. The membrane areas per unit cell volume (μm(2)/μm(3)) were: external sarcolemma 0.27, external sarcolemma + T-system 0.34, total sarcotubules 1.3. Diads made up 0.08 of sarcotubular volume and 0.12 of sarcotubular membrane area. 0.14 of the external sarcolemmal membrane area was involved in diadic complexes with underlying subsarcolemmal cisterns.